Uruguay : 2012 Article IV Consultation. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2013)
Uruguay's near-term outlook is positive, but with risks and policy challenges. Medium-term challenges include bolstering the economy's resilience to shocks and fostering productivity growth. Inflation is a priority and monetary policy cannot fight inflation alone; concerted efforts on other fronts are also necessary. Near-term fiscal policy could better support monetary policy. A long-term policy challenge is to bolster growth prospects and reduce output volatility. The political cycle should be propitious for continued sound policies and progress with reforms.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet